The Impact of Using the Strategies of Command Teaching and Cooperative Learning on Improving the Technical Performance of the Human Wheel and Forward Roll Skills from an Open Position in Gymnastics - Mohammad O'beidat, ماجدولين محمد (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aimed to identify the impact of using both the command teaching and cooperative learning strategies on improving the skills of Human Wheel and Forward Roll from an open position in gymnastics. The researcher adopted an empirical approach, and the study sample, which was selected intentionally, invoved (20) female students in the Faculty of Sports Science at Mutah university that enrolled in the course of Gymnastics (2) during the first semester of the academic year 2024/2025. The sample individuals were divided into two groups: the first experimental group (n=10), whose members were taught using the command teaching strategy, and the second experimental groups (n=10), whose members were taught using the cooperative learning strategy. The researcher used means, standard deviations, Pearson correlation coefficient, skewness coefficient, and t-test. The results showed that there are statistically significant differences between the pre-tests and post-tests in the command teaching strategy and cooperative learning strategy in improving the skills of Human Wheel and Forward Roll from an open position in gymnastics in favor of post-tests. The results showed that there are differences in the post tests between the command teaching and cooperative learning strategies to the advantage of the command teaching strategy regarding improving the skills of Human Wheel and Forward Roll from an open position in gymnastics. In the light of the results, the researcher recommended enhancing the use of command teaching strategy as one of the effective teaching strategies for gymnastics. The researcher also recommended training and improving practical subjects for teachers and students on the use of different strategies in the learning process.